Human’s Relationship with Technology in Nick Land’s Accelerationism - Wijarnarko, Andrean Ferry; Maharani, Septiana Dwiputri (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2024)
Technology exists as a manifestation of human awareness of fulfilling needs and helping with daily human activities. Even in their daily lives, humans cannot be separated from the existence of technology. The presence of technology encourages human access to solve various modern problems that are closely related to technology. This is emphasized by Nick Land that technology is an expression of the human drive to overcome the limitations of nature and improve the quality of nature, even humans. Technology is present as a way for humans to enhance their living conditions. Developments in this contemporary era are faced with further developments in the relationship between humans and technology, namely; technology has the potential to replace the role of humans in various fields. This research aims to explore the rapid advancement of technology through accelerationism, which can potentially influence humans in solving a problem related to human relations with technology. The research method used is philosophical hermeneutics on actual problems. Nick Land through accelerationism, provides a view that technological development must be accelerated and allowed to run. Land believes that technology will bring humans to the next stage of evolution to a better life. The problem of human relationships with accelerationism in technology can impact the development of human life. Humans and technology can work together for the benefit of mankind.